Sport4Me: A people focused approach to engaging Australians in sport - Eime, Rochelle; Westerbeek, Hans; Pill, Shane; Reece, Lindsey (Frontiers in Sports and Active Living, 2023)
The traditional model of community club-based sport is fine for those, particularly children and youth, who enjoy the competitive focus and have the skills and commitment to play. But societal preferences during leisure time have changed dramatically over recent decades. However, sport organisations have made limited progress in response to these changes in providing ways in which children and youth can participate outside the traditional competitive structures and environments. In this paper the context of community club-based structures is reviewed leading into an assessment of the associated impact of these structures on sport participation. Children and youth's current motivations to play sport including what makes sport fun to play, are considered. It is then demonstrated that the associations between motivations to play sport and the factors that contribute to fun and enjoyment, are often misaligned for many individuals, with a primary focus on competition-based structures to deliver community club sport. In the final part of the paper a model for community sport organisations where people are put first is proposed - Sport4Me. Sport4Me is about flexible, inclusive, equitable sporting opportunities that focus on friends, fun, physical literacy and play. The model would complement the traditional competitive club-based model and afford participants more choice whilst fostering an environment that promotes lifelong involvement in sport. This model will require structural and cultural changes to the sporting environment and include coaching practices. Sport4Me is an evidence-based model, but it is not radical in its conceptualisation but rather, builds on previously proposed approaches, considers the needs and wants of potential sport participants and widens the scope of sport delivery.